A new species of the genus Pethia from Mizoram, northeastern India (Teleostei: Cyprinidae) - Dishma, Mayanglambam; Vishwanath, Waikhom (Zootaxa, 2013)
The paper describes Pethia expletiforis, a new cyprinid species from the Ka-ao River, Kaladan drainage, Mizoram, India. It is distinguished from its congeners in the Chindwin-Irrawaddy and Ganga-Brahmaputra drainages by the combination of: a complete lateral line, nine predorsal scales, 12 circumpeduncular scales, ½4/1/3½ transverse scales, a black blotch on the caudal peduncle, and the absence of a humeral mark and barbels.